Antipsychotic Induced Dopamine Receptor Supersensitivity and It's Clinical Implications - Lazuardi, Riko; Rina, Khairina; Dianasari (Jurnal Psikiatri Surabaya, 2022)
Background : Schizophrenia is a serious mental disorder that requires multi-modal and continuous treatment, mainly with antipsychotic. Along with the increasing life expectancy of schizophrenic patients, various problems due to prolonged blocking of dopamine receptors have emerged, especially dopamin receptor supersensitivity and it's clinical implications.Aim : This study aims to determine the problems with long-term use of antipsycotics and the clinical implications of dopamine receptor supersensitivity..Methods : PubMed and Google Scholar were searched using the following keyword: (schizophrenia) AND (long term antipsychotic OR prolonged antipsychotic) AND ( D2 receptor OR dopamine-2 receptor) AND (supersensitivity) using the journal publication filter for the 2000-2019 issue. We also used textbooks published in the last 10 years and were related to writing themes.Review : Given their chronic nature, it is often necessary to give schizophrenia patient long-term antipsychotics. Prolonged blocking of D2 receptor can results variety of unpleasant effect, including dopamine receptor supersensitivity. This phenomenon can cause problematic implications such as dopamine supersensitivity psychosis, treatment-resistant schizophrenia and tardive dyskinesia. The risk of these side effects arises if antipsychotic use is not done wisely, such as the use of higher-than-recommended doses, antipsychotic polypharmacy, improper indications, and only rely on antipsychotics without maximizing the role of other therapeutic modalities. Summary : Clinicians need to pay attention to the rationality of the use of antipsychotics and conduct intensive supervision to reduce the risk of any clinical implications of dopamine receptor supersensitivity.Keywords: schizophrenia, long term antipsychotic, dopamine, receptor D2, supersensitivity.